PENENTUAN JUMLAH TENAGA KERJA PADA PROSES PEMBUATAN BATU BATA DENGAN METODE WORK LOAD ANALYSIS (WLA) GUNA MEMENUHI PERMINTAAN - Abdillah, Vicky Harisuddin; Purnama, Jaka (Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
UD Agung Barokah is a Small and Medium Enterprise (UKM) which produces red bricks. This UKM produces red bricks which are used for building construction such as housing walls, fences, warehouse walls and gutters. Labor is an important element in red brick production. To carry out production activities every day, the company must know the capacity of its employees because it has a big impact on the production process so that it is more optimal. The WLA method is used in analyzing labor needs to optimize the use of human resources. By calculating WLA, companies can measure the amount of labor needed to complete certain work. Meanwhile, aggregate planning is used to help companies plan production capacity to meet demand and according to existing capacity, with the lowest possible expenditure. The standard time for the process of making 1 unit of bricks which includes 5 divisions is 13.38 minutes. The initial workforce at the company was 10 workers, then data processing was carried out using the WorkLoad Analysis (WLA) method to fulfill the request obtained for 11 workers without doing overtime at a cost of Rp. 27,270,000,- with details from the division operator printing (O-1) only requires 1 worker. Meanwhile, calculations using capacity planning and production costs for the number of workers to meet demand produce results of 6 workers. The results after carrying out the labor planning calculations showed that the costs were IDR 23,566,000 and the labor costs before planning were IDR 25,200,000, in both calculations the labor costs were different.